Efficacy of chemical and non-chemical methods of weed management in rainfed potato (Solanum tuberosum) - YADAV, S K; LAL, S S; SRIVASTAVA, A K; BAG, T K; SINGH, B P (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during two consecutive summer season of 2011 and 2012 at Central Potato Research Station, Shillong to evaluate comparative efficacy of chemical and non-chemical methods of weed management in rainfed potato (Solanum tuberosum L.) cultivation of Meghalaya. Maximum reduction in crop yield due to presence of weed by 34.4% and 37.2% during first year and second year, respectively was found under weedy check plot followed by farmers' practices compared to weed free treatment. Application of metribuzin @ 1.0 kg ai/ha as pre emergence caused the highest reduction in total weed density and weed dry matter accumulation as compared to other herbicides during the both the years. However, the maximum weed control efficiency was observed under weed free treatment followed by application of metribuzin. The mean data of two year revealed that the maximum potato tuber yield (28.2 tonnes/ha) were recorded in the weed free followed by application of metribuzin @ 1 kg ai / ha. However, the net return and B:C ratio were significantly higher with the application of metribuzin @ 1 kg ai /ha.